A elasticidade de substituição de Morishima aplicadas aos recursos fósseis da matriz de energia primária - França, Wagner Wilson PInho de (2018)
The global primary energy mix is mostly composed by nonrenewable resources and the use of which uses contributes to increase the greenhouse gas emissions. The consumption of oil and coal, responsible for attending 60% of the total energy demand between 1970 and 2015, is more likely to enhance the air pollution than the consumption of natural gas. Besides, some authors announce the impossibility of sustaining the demand of oil with conventional type only at around 2050, because of technical and economic constraints over the reserves. Technology has been playing a roll giving more flexibility to the interfuel substitution among fossil fuels, in many applications. That gives the opportunity to increase the share of natural gas in the primary mix, while reducing the consumptions of the other two. Moreover, the reserves of natural gas are larger in comparison with the ones of oil, allowing it to alleviate the pressure over the latter. From those perspectives, increasing the use of natural gas would contribute to reduce the negative environment externality and the extension of a possible shock to be unleashed in the energy supply. The objective of this dissertation is to seek for a substitutability between natural gas and the others fossil fuels in the primary energy demand, using the Morishima Elasticity of Substitution, between 1970 and 2015. The model started with a Translog cost function to obtain the input demand equations of each fuel and their cost share functions, applying Shephard’s lemma. The parameters of the econometric regression were estimated by the Seemingly Unrelated Regressions method, as means to measure the price elasticity, the Allen Elasticity of Substitution and the Morishima Elasticity of Substitution. The model was applied to the United States due to their significance in the global context of energy. The results showed that a single conclusion for the period as a whole is statistically insignificant. Based on own-price elasticities, there were clearly three structural brakes, statistically significant, which divided the time series in four intervals. In the interval 1970-1981, the natural gas had a complementary relation with oil and both were substitutes for coal. In the intervals 1982-1995 and 1996-2008, there was substitutability among natural gas and oil, although limited. In the most recent interval, all of the fuels were complements to each other. Putting together the elasticities of substitution and the price elasticities analysis, we conclude that factors exogenous to the free market relations, such as government interventions, were determinants to demand decisions. The lack of a continuous and consistent relation of substitution between natural gas and the other two fossil fuels, warns that the concerns presented in this work may have being neglected and a transition from a polluted and finite mix to another cleaner and renewable, bridged by natural gas, is not occurring in the world’s largest economy.